1999
DOI: 10.1111/j.1348-0421.1999.tb02371.x
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Murine Model for Autoimmune Enterocolitis Using Klebsiella pneumoniae O3 Lipopolysaccharide as a Potent Immunological Adjuvant

Abstract: An experimental model for autoimmune enterocolitis was produced in mice by repeated immunization of homologous colon extract together with Klebsiella O3 lipopolysaccharide (KO3 LPS) as an immunological adjuvant. Histological changes in the intestinal lesions were characterized by infiltration with polymorphonuclear leukocytes in the lamina propria, muscularis mucosae and submucosa of repeatedly immunized mice. No such intestinal lesions were produced in mice receiving injections of colon extract alone or KO3 L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“… 20,21 It was previously demonstrated that LPS or its lipid A portion enhanced MRL/lpr nephritis in mice, 5 experimental autoimmune uveitis, 6 experimental autoimmune myocarditis 7 and experimental autoimmune enterocolitis. 8 However, few studies clearly showed a role for LPS in autoimmune arthritis.…”
Section: Discussionmentioning
confidence: 99%
“… 20,21 It was previously demonstrated that LPS or its lipid A portion enhanced MRL/lpr nephritis in mice, 5 experimental autoimmune uveitis, 6 experimental autoimmune myocarditis 7 and experimental autoimmune enterocolitis. 8 However, few studies clearly showed a role for LPS in autoimmune arthritis.…”
Section: Discussionmentioning
confidence: 99%
“…Collagen-induced enterocolitis [42] as well as arthritis [43] has been observed in experimental animals when immunized with homologous colonic extracts and collagen type II together with Klebsiella lipopolysaccharides.…”
Section: Aetiopathogenesismentioning
confidence: 99%
“…Increased levels of LPS are observed in obesity and other metabolic disorders as well as adipose tissue inflammation and pancreatic beta-cell dysfunction. For example, LPS has been shown to aggravate experimental autoimmune myocarditis (Kato et al, 1993), EAU (Yokochi et al, 1993) and experimental autoimmune enterocolitis (Paeng et al, 1999). In addition, LPS appears to play an important role as an adjuvant in the induction of autoimmune arthritis in a mouse model (Yoshino et al, 2000).…”
Section: The Role Of Microbial Metabolitesmentioning
confidence: 99%